Dutch Forensic Flexible Assertive Community Treatment: Operating on the Interface Between General Mental Health Care and Forensic Psychiatric Care - Smeekens, Marjam V.; Sappelli, Fedde; de Vries, Meike G.; Bulten, Berend H. (Frontiers in Psychology, 2021)
In the Netherlands, Forensic Flexible Assertive Community Treatment (ForFACT) is used as a specialized form of outpatient intensive treatment. This outreaching type of treatment is aimed at patients with severe and long lasting psychiatric problems that are at risk of engaging in criminal behavior. In addition, these patients often suffer from addiction and experience problems in different areas of their life (e.g. financial debt, unemployment, or lack of daytime activities). The aim of this exploratory study was to gain more insight into the characteristics of the ForFACT patient population. More knowledge about these patients may enhance the effectiveness of ForFACT and therefore (further) reduce the risk of recidivism. Data on 132 ForFACT patients were gathered by studying electronic patient records, criminal records, and by conducting semi-structured interviews with practitioners and patients. Additionally, as part of a cognitive screening, two screening instruments were conducted to gain insight into intelligence and possible mild cognitive impairments. This article gives a broad description of the ForFACT patient population, including demographic data and context variables, diagnostics, recidivism risk and offense history, and aspects related to care. Furthermore, several recommendations are given to further improve ForFACT. Based on the results it can be concluded that the ForFACT patient population shows a high degree of diversity in complex care needs and responsivity issues. Therefore, this article highlights the necessity for ForFACT to collaborate with other mental health institutions. Moreover, it is important to continually check the inclusion and exclusion criteria when admitting patients to ForFACT, and to examine whether ForFACT is still the most adequate care for patients or if they need to be referred. In addition, the results emphasize the importance of cognitive screening for forensic outpatients. Finally, this study zooms in on the interface between forensic psychiatric care and general mental health care.